BK Virus RNA in Renal Allograft Biopsies. (May 2020) - Costigliolo, Francesca; Lombardo, Kara; Arend, Lois J.; Rosenberg, Avi Z.; Matoso, Andres; Carter-Monroe, Naima; Bagnasco, Serena M.
BK polyomavirus–associated nephropathy (BKpyVAN) remains a cause of graft loss in kidney transplant recipients on immunosuppressive therapy. Its diagnosis relies on the identification of BK virus (BKV) in the renal allograft biopsy by positive immunohistochemical (IHC) stain for the viral SV40 large T antigen, although in situ hybridization (ISH) for viral DNA is used in some centers. We examined tissue detection of BKV RNA by RNAscope, a novel, automated ISH test, in 61 allograft biopsies from 56 patients with BKpyVAN. We found good correlation between the estimate of BKV tissue load by RNAscope ISH and SV40 IHC ( R 2 = 0.65, p< 0.0001). RNAscope ISH showed 88% sensitivity and 79% specificity and, as an alternative test, could confirm the presence of BKV tissue in presumed BKpyVAN and rule out BKV as the causative agent in JC virus nephropathy. We also used tissue BK viral load estimates by both RNAscope ISH and SV40 IHC to examine the relation between tissue and plasma BK levels and found significant correlation only between BK viremia and tissue BK measured by RNAscope ISH. Our findings suggest that the RNAscope ISH assay could be a reliable test for BKV detection in allograft biopsies.